PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 7E BERBANTUAN GOOGLE SITES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Ananda Nadhifah Yustikarinda; Syaiful Hadi; Ummu Sholihah; Eni Setyowati (STKIP Subang, 2026)
Students' mathematical problem-solving skills in Indonesia remain relatively low, as reflected by PISA results where over 70% of students score below Level 2. A similar condition was found among seventh-grade students regarding triangle similarity, allegedly caused by teacher-centered instruction and a lack of interactive digital media. This study aims to examine the effect of the 7E Learning Cycle model assisted by Google Sites on students' mathematical problem-solving abilities. Employing a quantitative approach with a one-group pretest-posttest design, the sample consisted of 30 seventh-grade students selected through simple random sampling. Data were collected using essay tests based on Polya's indicators, validated by experts, and analyzed descriptively and inferentially using the Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, and N-Gain analysis. The results showed an increase in the mean score from a pretest of 21.47 (SD = 10.00) to a posttest of 44,93 (SD = 18,34). The Wilcoxon Signed Rank Test yielded with (), indicating a significant difference between the initial and final scores with a large effect size (). Meanwhile, the mean N-Gain score was 0,29, classified as low, although 43,33% of students reached the moderate category. These findings demonstrate that the 7E Learning Cycle model assisted by Google Sites has a significant effect on improving students' mathematical problem-solving skills. The model is recommended as an alternative instructional strategy, with future studies suggested to include a control group to strengthen causal evidence.